2017
DOI: 10.1371/journal.pone.0184567
|View full text |Cite
|
Sign up to set email alerts
|

The heuristics of nurse responsiveness to critical patient monitor and ventilator alarms in a private room neonatal intensive care unit

Abstract: AimAlarm fatigue is a well-recognized patient safety concern in intensive care settings. Decreased nurse responsiveness and slow response times to alarms are the potentially dangerous consequences of alarm fatigue. The aim of this study was to determine the factors that modulate nurse responsiveness to critical patient monitor and ventilator alarms in the context of a private room neonatal intensive care setting.MethodsThe study design comprised of both a questionnaire and video monitoring of nurse-responsiven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 23 publications
1
44
0
Order By: Relevance
“…34–36 In particular, the ECRI Institute highlights that collecting and analysing ventilator data can be challenging, and limited research exists on ventilator alarms. 19 24 37 To the best of our knowledge, this study is the largest audit of ventilator alarms, and we show that the daily alarm pressure (average) because of ventilators, in fact, exceeds that due to patient monitors alone. It should be noted that although on average ventilator alarm pressure is high, it is also dependent on the mode of ventilation.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…34–36 In particular, the ECRI Institute highlights that collecting and analysing ventilator data can be challenging, and limited research exists on ventilator alarms. 19 24 37 To the best of our knowledge, this study is the largest audit of ventilator alarms, and we show that the daily alarm pressure (average) because of ventilators, in fact, exceeds that due to patient monitors alone. It should be noted that although on average ventilator alarm pressure is high, it is also dependent on the mode of ventilation.…”
Section: Discussionmentioning
confidence: 68%
“…In a previous study carried out in the SFR NICU of MMC, we identified that the median nurse response times to red desaturation alarms was quite long at 56 s. 19 Since extended desaturation events are associated with adverse outcomes, there is a natural tendency for SFR NICUs to err on the side of caution and opt for shorter delays. 27 However, for the OBA NICUs with direct visual oversight and potentially shorter distances and nurse response times, slightly longer delays in generating the alarm, on average, help in reducing the mean daily duration for which the alarms sound and reduce noise in the typically noisier OBA environment.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The fact that motor response often precedes changes in vital signs can be exploited for the early generation of alarms – an important issue in the NICU – potentially increasing the window of opportunity for nurses to respond to critical alarms [39] , [40] . Literature also shows that spontaneous movement can lead to various physiological perturbations, including increased oxygen consumption due to metabolic demands, movement-induced hyperventilation, and hypocapnia.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have only recently been exploring the phenomenon of alarm fatigue (Alsaad et al, 2017;Bonafide et al, 2014;Cho et al, 2016;Deb and Claudio, 2015;Drew et al, 2014;Funk et al, 2016;Gazarian et al, 2015;Honan et al, 2015;Joshi et al, 2017;Varpio et al, 2012), and most of this research emanates from North America. This could in part be explained by the different nurse-patient ratios between the US and elsewhere and the practice of nursing patients in single rooms rendering American nurses more reliant on alarms to monitor their patients.…”
Section: Introductionmentioning
confidence: 99%